Discovery of a novel fluorescent chemical probe suitable for evaluation of neuropilin‐1 binding of small molecules. Issue 4 (20th January 2020) - Conole, Daniel; Chou, Yi‐Tai; Patsiarika, Anastasia; Nwabo, Valery; Dimitriou, Eleni; Soudy, Christelle; Mota, Filipa; Djordjevic, Snezana; Selwood, David L.
Abstract: Neuropilin‐1 (NRP1) is emerging as an important molecule in immune signaling where it has been shown to modulate the actions of TGF‐β1 in macrophages and regulatory T cells. The development of cost‐effective and reliable assays for NRP1 binding is therefore important. We synthesized three new NRP1 small molecule fluorophores and examined their performance as fluorescent polarization probes. One molecule DS108 exhibited favorable binding and fluorescent characteristics and allowed us to establish a simple assay suitable for medium to high throughput screening of small molecules.